A Minimum Mean-Square-Error Noise Reduction Algorithm on Mel-Frequency Cepstra for Robust Speech Recognition - Yu, Dong; Deng, Li; Droppo, Jasha; Wu, Jian; Gong, Yifan; Acero, Alex (Proc. ICASSP, 2008)
We present a non-linear feature-domain noise reduction algorithm based on the minimum mean square error (MMSE) criterion on Mel-frequency cepstra (MFCC) for environment-robust speech recognition. Distinguishing from the MMSE enhancement in log spectral amplitude proposed by Ephraim and Malah (E&M) [7], the new algorithm presented in this paper develops the suppression rule that applies to power spectral magnitude of the filter-banks’ outputs and to MFCC directly, making it demonstrably more effective in noise-robust speech recognition. The noise variance in the new algorithm contains a significant term resulting from instantaneous phase asynchrony between clean speech and mixing noise, missing in the E&M algorithm. Speech recognition experiments on the standard Aurora-3 task demonstrate a reduction of word error rate by 48% against the ICSLP02 baseline, by 26% against the cepstral mean normalization baseline, and by 13% against the conventional E&M log-MMSE noise suppressor. The new algorithm is also much more efficient than E&M noise suppressor since the number of the channels in the Mel-frequency filter bank is much smaller (23 in our case) than the number of bins in the FFT domain (256). The results also show that our algorithm performs slightly better than the ETSI AFE on the well-matched and mid-mismatched settings.